PHA (Polyhydroxyalkanoate) composition with high film spraying speed and high paper-plastic composite strength and preparation method of PHA composition

By adding graphene nano -hybrids and alkaline metal compounds to polycaticated fatty acid ester (PHA), the problem of insufficient mechanical strength and poor gas blockage of PHA, and a higher composite strength and gonorrhea speed.

CN119371793AInactive Publication Date: 2025-01-28NINGBO HOMELINK ECO ITECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411919425.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-01-28
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Polyhydroxy fatty acid esters (PHA) have problems such as insufficient mechanical strength, high brittleness and poor gas barrier properties in applications, which limits their widespread use in packaging and other applications.

Method used

By adding two -dimensional graphene nano -hybrids and alkaline metal compounds to PHA, PHA's crystal density and crystallization rate are improved, thereby improving its mechanical strength and gas blocking performance.

Benefits of technology

It significantly improves PHA's mechanical strength and gas blocking performance, and improves its application potential in packaging and other applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CHRGUKVXGOOPVAAFRJ1G5MXIW9CMYPP3BNBBDTIW
    Figure CHRGUKVXGOOPVAAFRJ1G5MXIW9CMYPP3BNBBDTIW
Patent Text Reader

Abstract

The invention relates to the technical field of functional degradable polyhydroxyalkanoate materials, in particular to a PHA composition with high lamination speed and high paper-plastic composite strength and a preparation method of the PHA composition. The invention relates to a PHA (Polyhydroxyalkanoate) composition with high lamination speed and high paper-plastic composite strength, which is prepared from the following raw materials in parts by mass: 85 to 95 parts of polyhydroxyalkanoate, 6 to 10 parts of N-(2-(methacryloyloxy) ethyl)-N, N-dimethyldodecane-1-ammonium bromide-graphene nano hybrid and 0.5 to 1.5 parts of alkali metal compound, the alkali metal compound is one of potassium hydroxide, potassium acetate and fluoro binary sulfimide potassium. The PHA composition disclosed by the invention has excellent composite strength, relatively high film spraying speed and excellent antibacterial property and gas barrier property.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of functional degradable polyhydroxyalkanoate materials, and more specifically, to a PHA composition with high lamination speed and high paper-plastic composite strength and a preparation method thereof. Background Art

[0002] Plastic products are widely used in industrial production and life due to their wide sources, beautiful appearance, light weight and low price, easy processing and stable properties. However, traditional petroleum-based plastic products are difficult to degrade on their own in the natural environment, and the large amount of waste after use is difficult to recycle, which in turn has a great negative impact on the ecological environment.

[0003] Polyhydroxyalkanoates (PHA) are a type of biodegradable polymer synthesized by microbial fermentation. They can be degraded by composting and seawater. Composting can also produce fertile soil. Moreover, polyhydroxyalkanoates (PHA) have excellent biocompatibility and mechanical properties and can be processed into films, straws, tableware, medical stents and daily products. Therefore, polyhydroxyalkanoates are expected to partially replace traditional petroleum-based plastics.

[0004] However, polyhydroxyalkanoates (PHA) still have problems such as slow crystallization rate, large crystal size, and poor nucleus density, which result in insufficient mechanical strength. At the same time, they are relatively brittle and have poor gas barrier properties, which seriously limit the application of polyhydroxyalkanoates. Therefore, there is an urgent need for a polyhydroxyalkanoate composition with better composite strength. Summary of the invention

[0005] In order to improve the defect of insufficient composite strength of conventional polyhydroxyalkanoate compositions, the present application provides a PHA composition with high lamination speed and high paper-plastic composite strength and a preparation method thereof.

[0006] In the first aspect, the present application provides a PHA composition with high lamination speed and high paper-plastic composite strength, which adopts the following technical solution: A PHA composition with high lamination speed and high paper-plastic composite strength comprises the following raw materials in parts by mass: 85-95 parts of polyhydroxyalkanoate, 6-10 parts of N-(2-(isobutylene acyloxy)ethyl)-N,N-dimethyldodecane-1-ammonium bromide-graphene nanohybrid and 0.5-3 parts of alkali metal compound, wherein the alkali metal compound is one of potassium hydroxide, potassium acetate and potassium fluorodisulfonyl imide.

[0007] Two-dimensional graphene sheets have extremely high aspect ratios, high gas reverse permeability and super mechanical strength. Therefore, when graphene is added to polyhydroxyalkanoates, the mechanical strength and gas barrier properties of polyhydroxyalkanoates will be significantly improved. The reason is that the addition of graphene can increase the crystal nucleus density of polyhydroxyalkanoates, thereby increasing the crystallization rate and crystallinity of polyhydroxyalkanoates, and the increase in crystallinity can significantly improve the gas barrier properties of polyhydroxyalkanoates.

[0008] However, graphene has a large specific surface area, is easy to agglomerate, and is difficult to be evenly dispersed in the polyhydroxyalkanoate matrix, thus failing to achieve the expected modification effect. In the present application, N-(2-(isobutyleneoxy)ethyl)-N,N-dimethyldodecane-1-ammonium bromide is grafted onto the graphene surface through coupling reaction and free radical copolymerization, which improves the dispersion performance of graphene and obtains excellent antibacterial properties. The antibacterial mechanism of N-(2-(isobutyleneoxy)ethyl)-N,N-dimethyldodecane-1-ammonium bromide-graphene nanohybrid is that N-(2-(isobutyleneoxy)ethyl)-N,N-dimethyldodecane-1-ammonium bromide-graphene nanohybrid contains quaternary ammonium salt components, and quaternary ammonium salts can destroy the integrity of bacterial cell membranes, interfere with the metabolic process in bacterial cells, and affect the replication and transcription of bacterial nucleic acids, thereby being more suitable for the packaging coating field.

[0009] In the field of packaging coating, the coating speed of the material is extremely important. However, even though N-(2-(isobutyleneoxy)ethyl)-N,N-dimethyldodecane-1-ammonium bromide-graphene nanohybrid has excellent compatibility with polyhydroxyalkanoates, the viscosity of the PHA composition finally obtained is still inevitably increased, thereby affecting the coating speed of the PHA composition.

[0010] However, since polyhydroxyalkanoates are natural macromolecular biomaterials synthesized by microorganisms, their melt flow rate cannot be adjusted through a polymerization process like chemically polymerized macromolecular materials. In the prior art, chemical depolymerization is usually used to reduce the molecular weight of polyhydroxyalkanoates, thereby improving the fluidity of polyhydroxyalkanoates. However, the above method has a complicated process and is easy to introduce a depolymerization catalyst or initiator with poor compatibility, thereby affecting the mechanical strength or other properties of polyhydroxyalkanoates.

[0011] In the present application, an alkali metal compound is added to the polyhydroxyalkanoate. Since the thermal motion of the polyhydroxyalkanoate in the molten state is relatively strong, the alkali metal compound can directly act on the main chain ester bond of the polyhydroxyalkanoate to break it, thereby reducing the molecular weight of the polyhydroxyalkanoate and promoting the melt flow rate of the PHA composition to increase.

[0012] Preferably, the preparation method of the N-(2-(isomethacryloyloxy)ethyl)-N,N-dimethyldodecane-1-ammonium bromide-graphene nanohybrid is: First, 0.4-0.6 g of γ-methacryloyloxypropyltrimethoxysilane modified graphene is dispersed in 40-60 ml of n-butanol under a nitrogen atmosphere, and then 5-10 mg of benzoyl peroxide and 0.5-1.0 g of N-(2-(isobutylene oxy)ethyl)-N,N-dimethyldodecane-1-ammonium bromide are added in sequence. The temperature is raised to 70-90°C and the reaction is continued for 24 hours. Finally, the mixture is washed and freeze-dried to obtain N-(2-(isobutylene oxy)ethyl)-N,N-dimethyldodecane-1-ammonium bromide-graphene nanohybrid.

[0013] Preferably, the preparation method of the γ-methacryloxypropyltrimethoxysilane modified graphene is: First, 8-12 ml of γ-methacryloxypropyltrimethoxysilane is dissolved in 80-120 ml of methanol-deionized water solution at room temperature, and the volume ratio of methanol to deionized water is (8-10):1. After it is fully dissolved, 0.8-1.2 g of graphene is added, the temperature is raised to 100-120°C and reacted for 12 hours, and finally washed and freeze-dried to obtain γ-methacryloxypropyltrimethoxysilane modified graphene.

[0014] Preferably, the preparation method of N-(2-(isobutylene oxy)ethyl)-N,N-dimethyldodecane-1-ammonium bromide is: First, 15-25 mmol of dimethylaminoethyl methacrylate and 15-25 mmol of 1-bromododecane are dissolved in 4-8 ml of ethanol, then the temperature is raised to 60-80°C and reacted for 12 hours, then recrystallized in ethanol, and finally freeze-dried to obtain N-(2-(isobutylene oxy)ethyl)-N,N-dimethyldodecane-1-ammonium bromide.

[0015] Preferably, the method for preparing the graphene is: First, add 2-4g of graphite flakes and 1-2g of sodium nitrate to 50-80ml of concentrated sulfuric acid, then cool the mixture to 0°C, then slowly add 5-10g of potassium permanganate to the mixture, keeping the temperature below 20°C during the addition process; After the addition is completed, the temperature is raised to 30-40°C, the reaction is continued for 20-40 minutes, and then 100-150 ml of deionized water is added dropwise, and the reaction is carried out at a temperature of 90-100°C for 12-18 minutes, and then 400-450 ml of deionized water and 2-4 ml of hydrogen peroxide are added, and finally dialyzed, filtered, washed, and freeze-dried to obtain graphene.

[0016] Preferably, the alkali metal compound is potassium fluorodisulfonyl imide.

[0017] Among potassium hydroxide, potassium acetate and potassium fluorinated disulfonyl imide, potassium acetate and potassium fluorinated disulfonyl imide contain organic groups. Therefore, compared with potassium hydroxide, potassium acetate or potassium fluorinated disulfonyl imide have better compatibility with polyhydroxyalkanoates, thereby enabling the alkali metal compound to act more accurately on the ester bond of the polyhydroxyalkanoates, thereby enabling the prepared PHA composition to have a better melt flow rate.

[0018] Of potassium acetate and potassium fluorinated disulfonyl imide, potassium fluorinated disulfonyl imide has both a higher cation mass ratio and a higher flexible conjugated structure, thereby obtaining a better cation migration performance, that is, the reaction activity of potassium fluorinated disulfonyl imide is better, thereby enabling the PHA composition to still have an extremely good melt flow rate at a lower alkali metal compound addition amount.

[0019] Preferably, the preparation method of the potassium fluorodisulfonyl imide comprises the following steps: Preparation of potassium trifluoromethylsulfonamide: First, 95-105g of trifluoromethylsulfonamide was mixed with 450-550ml of deionized water, and then 40-60ml of potassium hydroxide aqueous solution was slowly added dropwise, and the concentration of the potassium hydroxide aqueous solution was 0.8g / ml. The mixture was stirred for 6h, and finally filtered and concentrated to obtain potassium trifluoromethylsulfonamide; Preparation of (trifluoromethylsulfonyl)(chlorosulfonyl)imide: First, 35-45g of trifluoromethylsulfonamide, 70-76g of thionyl chloride and 40-46g of chlorosulfonic acid are mixed, then the temperature is raised to 110-130°C, and the excess thionyl chloride is distilled off after reflux for 45h, and the excess chlorosulfonic acid is distilled off under reduced pressure at 90°C, and finally the temperature is raised to 120°C and distilled off under reduced pressure to obtain solid (trifluoromethylsulfonyl)(chlorosulfonyl)imide; Preparation of Potassium Fluorodisulfonyl Imide: First, 12-16 g (trifluoromethylsulfonyl) (chlorosulfonyl) imine, 10-12 g trifluoromethylsulfonamide potassium, 8-12 g pyridine and 90-110 ml acetonitrile are mixed, then the temperature is raised to 70-90 ° C and stirred for 24 hours, and then the insoluble matter is removed by suction filtration, and the filtrate is concentrated under reduced pressure to obtain a solid product; The yellow product was then washed with methyl tert-butyl ether, and then vacuum dried at 60°C for 12 hours. Then, 18-22 g of potassium phosphate and 90-110 ml of acetonitrile were added at 40°C, and the mixture was reacted for 8 hours. Finally, the insoluble matter was removed by filtration, and the filtrate was concentrated under reduced pressure to obtain solid potassium fluorodisulfonyl imide.

[0020] Preferably, the PHA composition with high lamination speed and high paper-plastic composite strength comprises the following raw materials in parts by mass: 90 parts of polyhydroxyalkanoate, 8 parts of N-(2-(isobutylene acyloxy)ethyl)-N,N-dimethyldodecane-1-ammonium bromide-graphene nanohybrid and 1 part of potassium fluorodisulfonyl imide.

[0021] When N-(2-(isobutyleneoxy)ethyl)-N,N-dimethyldodecane-1-ammonium bromide-graphene nanohybrid and potassium fluorinated disulfonyl imide are added in the above-mentioned amounts, the prepared PHA composition will have excellent composite strength, faster coating speed, excellent antibacterial properties and gas barrier properties.

[0022] In a second aspect, the present application provides a method for preparing a PHA composition with high lamination speed and high paper-plastic composite strength, using the following technical solution: A method for preparing a PHA composition with high laminating speed and high paper-plastic composite strength comprises the following steps: S1. First, polyhydroxyalkanoate, N-(2-(isobutyleneoxy)ethyl)-N,N-dimethyldodecane-1-ammonium bromide-graphene nanohybrid and alkali metal compound are mixed, and then added into a twin-screw extruder for melt blending, with a melt temperature of 160-170° C. and a screw speed of 300-500 r / min, followed by extrusion granulation to obtain a crude product; S2. After drying the crude product, heat it in a water bath for 1-2 hours at a water bath temperature of 40-60° C., and finally dry it again to obtain a PHA composition with high lamination speed and high paper-plastic composite strength.

[0023] In summary, this application has the following beneficial effects: 1. Two-dimensional graphene sheets have extremely high aspect ratios, high gas reverse permeability and super mechanical strength. Therefore, when graphene is added to polyhydroxyalkanoates, the mechanical strength and gas barrier properties of polyhydroxyalkanoates will be significantly improved. The reason is that the addition of graphene can increase the crystal nucleus density of polyhydroxyalkanoates, thereby increasing the crystallization rate and crystallinity of polyhydroxyalkanoates, and the increase in crystallinity can significantly improve the gas barrier properties of polyhydroxyalkanoates.

[0024] 2. In the present application, N-(2-(isomethacryloyloxy)ethyl)-N,N-dimethyldodecane-1-ammonium bromide is grafted onto the surface of graphene through coupling reaction and free radical copolymerization, which improves the dispersion performance of graphene and obtains excellent antibacterial properties. The antibacterial mechanism of N-(2-(isomethacryloyloxy)ethyl)-N,N-dimethyldodecane-1-ammonium bromide-graphene nanohybrid is that N-(2-(isomethacryloyloxy)ethyl)-N,N-dimethyldodecane-1-ammonium bromide-graphene nanohybrid contains quaternary ammonium salt components, and quaternary ammonium salts can destroy the integrity of bacterial cell membranes, interfere with the metabolic process in bacterial cells, and affect the replication and transcription of bacterial nucleic acids, thereby being more suitable for the field of packaging coating.

[0025] 3. In the present application, an alkali metal compound is added to the polyhydroxyalkanoate. Since the thermal motion of the polyhydroxyalkanoate in the molten state is relatively strong, the alkali metal compound can directly act on the main chain ester bond of the polyhydroxyalkanoate to break it, thereby reducing the molecular weight of the polyhydroxyalkanoate and promoting the melt flow rate of the PHA composition.

[0026] 4. Potassium acetate or potassium fluorinated disulfonyl imide has better compatibility with polyhydroxyalkanoates, so that the alkali metal compound can act more accurately on the ester bond of polyhydroxyalkanoates, and potassium fluorinated disulfonyl imide has both a higher cationic mass ratio and a higher flexible conjugated structure, thereby obtaining better cationic migration performance, that is, the reaction activity of potassium fluorinated disulfonyl imide is better, so that the PHA composition still has an extremely good melt flow rate at a lower alkali metal compound addition amount. DETAILED DESCRIPTION

[0027] The present application is further described in detail below in conjunction with Examples 1-6 and Comparative Examples 1-3.

[0028] raw material Polyhydroxyalkanoates Wuhan Lanabai Pharmaceutical Chemicals; Potassium hydroxide CAS: 1310-58-3; Potassium acetate CAS: 127-08-2; n-Butanol CAS: 71-36-3; Benzoyl peroxide CAS: 94-36-0; γ-Methacryloyloxypropyltrimethoxysilane CAS: 2530-85-0; Methanol CAS: 67-56-1; Dimethylaminoethyl methacrylate CAS: 2867-47-2; 1-bromododecane CAS: 143-15-7; ethanol CAS: 64-17-5; graphite flakes Shijiazhuang Mayue Building Materials; sodium nitrate CAS: 7631-99-4; concentrated sulfuric acid CAS: 7664-93-9; trifluoromethylsulfonamide CAS: 421-85-2; thionyl chloride CAS: 7719-09-7; chlorosulfonic acid CAS: 7790-94-5; pyridine CAS: 110-86-1; acetonitrile CAS: 75-05-8; Potassium phosphate CAS: 7778-53-2.

[0029] Example 1 A PHA composition with high lamination speed and high paper-plastic composite strength comprises the following raw materials: 90g of polyhydroxyalkanoate, 8g of N-(2-(isobutylene acyloxy)ethyl)-N,N-dimethyldodecane-1-ammonium bromide-graphene nanohybrid and 1g of potassium hydroxide.

[0030] The preparation method of N-(2-(isobutylene acyloxy)ethyl)-N,N-dimethyldodecane-1-ammonium bromide-graphene nanohybrid is as follows: First, 0.5 g of γ-methacryloyloxypropyltrimethoxysilane modified graphene was dispersed in 50 ml of n-butanol under a nitrogen atmosphere, and then 8 mg of benzoyl peroxide and 0.8 g of N-(2-(isobutyleneoxy)ethyl)-N,N-dimethyldodecane-1-ammonium bromide were added in sequence. The temperature was raised to 80°C and the reaction was continued for 24 hours. Finally, the mixture was washed and freeze-dried to obtain N-(2-(isobutyleneoxy)ethyl)-N,N-dimethyldodecane-1-ammonium bromide-graphene nanohybrid.

[0031] The preparation method of γ-methacryloxypropyltrimethoxysilane modified graphene is: First, 10 ml of γ-methacryloxypropyltrimethoxysilane was dissolved in 100 ml of methanol-deionized water solution at room temperature, the volume ratio of methanol to deionized water was 9:1, and 1 g of graphene was added after it was fully dissolved. The temperature was raised to 110°C and reacted for 12 hours. Finally, it was washed and freeze-dried to obtain γ-methacryloxypropyltrimethoxysilane-modified graphene.

[0032] The preparation method of N-(2-(isobutylene acyloxy)ethyl)-N,N-dimethyldodecane-1-ammonium bromide is as follows: First, 20 mmol of dimethylaminoethyl methacrylate and 20 mmol of 1-bromododecane were dissolved in 6 ml of ethanol, then the temperature was raised to 70°C and reacted for 12 hours, then recrystallized in ethanol, and finally freeze-dried to obtain N-(2-(isobutylene acyloxy)ethyl)-N,N-dimethyldodecane-1-ammonium bromide.

[0033] The preparation method of graphene is: First, add 3g of graphite flakes and 1.5g of sodium nitrate to 70ml of concentrated sulfuric acid, then cool the mixture to 0°C, then slowly add 8g of potassium permanganate to the mixture, keeping the temperature below 20°C during the addition process; After the addition is completed, the temperature is raised to 35°C, the reaction is continued for 30 minutes, and then 120 ml of deionized water is added dropwise, and the reaction is carried out at 95°C for 16 minutes. Then 420 ml of deionized water and 3 ml of hydrogen peroxide are added, and finally dialyzed, filtered, washed, and freeze-dried to obtain graphene.

[0034] The preparation method of a PHA composition with high lamination speed and high paper-plastic composite strength comprises the following steps: S1. First, polyhydroxyalkanoate, N-(2-(isobutyleneoxy)ethyl)-N,N-dimethyldodecane-1-ammonium bromide-graphene nanohybrid and potassium hydroxide are mixed, and then added into a twin-screw extruder for melt blending, with a melt temperature of 165° C. and a screw speed of 400 r / min, and then extruded and granulated to obtain a crude product; S2. After drying the crude product, heat it in a water bath for 1.5 hours at a water bath temperature of 50° C., and finally dry it again to obtain a PHA composition with a high lamination speed and high paper-plastic composite strength.

[0035] Example 2 The difference from Example 1 is that potassium hydroxide is replaced by potassium acetate in the same amount.

[0036] Example 3 The difference from Example 1 is that potassium hydroxide is replaced by the same amount of potassium fluorodisulfonyl imide; The preparation method of potassium fluorinated disulfonyl imide comprises the following steps: Preparation of potassium trifluoromethylsulfonamide: First, 100g of trifluoromethylsulfonamide was mixed with 500ml of deionized water, and then 50ml of potassium hydroxide aqueous solution was slowly added dropwise, and the concentration of the potassium hydroxide aqueous solution was 0.8g / ml. The mixture was stirred for 6h, and finally filtered and concentrated to obtain potassium trifluoromethylsulfonamide; Preparation of (trifluoromethylsulfonyl)(chlorosulfonyl)imide: First, 40g of trifluoromethylsulfonamide, 73g of thionyl chloride and 43g of chlorosulfonic acid were mixed, then heated to 120°C, refluxed for 45h and then distilled to remove the excess thionyl chloride, then distilled under reduced pressure at 90°C to remove the excess chlorosulfonic acid, and finally heated to 120°C and distilled under reduced pressure to obtain solid (trifluoromethylsulfonyl)(chlorosulfonyl)imide; Preparation of Potassium Fluorodisulfonyl Imide: First, 14 g (trifluoromethylsulfonyl) (chlorosulfonyl) imine, 11 g potassium trifluoromethylsulfonamide, 10 g pyridine and 100 ml acetonitrile were mixed, then heated to 80 °C and stirred for 24 h, then filtered to remove insoluble matter, and the filtrate was concentrated under reduced pressure to obtain a solid product; The yellow product was then washed with methyl tert-butyl ether, and then vacuum dried at 60°C for 12 hours. Then, 20 g of potassium phosphate and 100 ml of acetonitrile were added at 40°C, and the mixture was mixed and reacted for 8 hours. Finally, the insoluble matter was removed by filtration, and the filtrate was concentrated under reduced pressure to obtain solid potassium fluorodisulfonyl imide.

[0037] Example 4 The difference from Example 1 is that the amount of potassium hydroxide added is 3 g.

[0038] Example 5-Example 6 The difference from Example 3 is that the addition amounts of the components of the PHA composition with high lamination speed and high paper-plastic composite strength are different, as shown in Table 1.

[0039] Table 1 Addition amount of each component of the PHA composition of Example 3 and Example 5-Example 6 (g) Example 3 Example 5 Example 6 Polyhydroxyalkanoates 90 95 85 N-(2-(Isobutyleneoxy)ethyl)-N,N-dimethyldodecane-1-ammonium bromide-graphene nanohybrid 8 6 10 Potassium fluorodisulfonyl imide 1 1.5 0.5 Comparative Example 1 A PHA composition consisting solely of polyhydroxyalkanoate.

[0040] Comparative Example 2 A PHA composition includes the following raw materials by mass: 90 g of polyhydroxyalkanoate and 8 g of graphene; The preparation method of the PHA composition comprises the following steps: S1. First, polyhydroxyalkanoate and graphene are mixed, and then added into a twin-screw extruder for melt blending, with a melt temperature of 165° C. and a screw speed of 400 r / min, followed by extrusion granulation to obtain a crude product; S2. After drying the crude product, heat it in a water bath for 1.5 hours at a water bath temperature of 50° C., and finally dry it again to obtain a PHA composition with a high lamination speed and high paper-plastic composite strength.

[0041] Comparative Example 3 A PHA composition includes the following raw materials by weight: 90 g of polyhydroxyalkanoate, 8 g of graphene, and 1 g of potassium hydroxide; The preparation method of the PHA composition comprises the following steps: S1. First, polyhydroxyalkanoate, graphene and potassium hydroxide are mixed, and then added into a twin-screw extruder for melt blending, with a melt temperature of 165° C. and a screw speed of 400 r / min, followed by extrusion granulation to obtain a crude product; S2. After drying the crude product, heat it in a water bath for 1.5 hours at a water bath temperature of 50° C., and finally dry it again to obtain a PHA composition with a high lamination speed and high paper-plastic composite strength.

[0042] Performance testing Tensile strength test Three samples were taken from each of Examples 1 to 6 and Comparative Examples 1 to 3, and then the tensile strength of the samples was tested by a universal material testing machine according to ISO527-2:2012 at a test speed of 50 mm / min, and the test data were averaged.

[0043] 2. Melt flow rate test Three samples were taken from Examples 1 to 6 and Comparative Examples 1 to 3, respectively, and then the melt flow rates of the samples were tested by a melt flow rate tester according to ISO1133-1:2011. The test temperature was 365° C., the test mass was 5 kg, and the test data were averaged.

[0044] The test data are shown in Table 2.

[0045] Table 2 Test data table of Examples 1-6 and Comparative Examples 1-3 Referring to Comparative Examples 1 and 2 and in combination with Table 2, it can be seen that the tensile strength of Comparative Example 2 is significantly improved compared with Comparative Example 1, which shows that the addition of graphene can significantly improve the mechanical properties of the PHA composition.

[0046] The reason is that the PHA composition has problems such as slow crystallization speed, large crystal size, and poor crystal nucleus density, so its mechanical strength is insufficient and it is relatively brittle. The two-dimensional graphene sheet has an extremely high aspect ratio, high gas reverse permeability and super mechanical strength. Therefore, when graphene is added to the PHA composition, the mechanical strength and gas barrier properties of the PHA composition will be significantly improved. The reason is that the addition of graphene can increase the crystal nucleus density of the PHA composition, thereby increasing the crystallization rate and crystallinity of the PHA composition, and the increase in crystallinity can significantly improve the gas barrier properties of the PHA composition.

[0047] However, it can be seen from Table 2 that the melt flow rate of Comparative Example 2 is also significantly reduced compared with Comparative Example 1. The reason is that graphene has a large specific surface area, is easy to agglomerate, and is difficult to be evenly dispersed in the polyhydroxyalkanoate matrix, which leads to an increase in the viscosity of the PHA composition, thereby affecting its coating speed.

[0048] Referring to Comparative Examples 2 and 3 and in combination with Table 2, it can be seen that the melt flow rate of Comparative Example 3 is significantly improved compared with Comparative Example 2, and at the same time, the tensile strength of Comparative Example 3 is only slightly decreased, which shows that the addition of alkali metal compounds can effectively improve the coating speed of the PHA composition.

[0049] The reason is that polyhydroxyalkanoates have strong thermal motion in the molten state. Therefore, the alkali metal compound can directly act on the main chain ester bond of polyhydroxyalkanoates to break it, thereby reducing the molecular weight of polyhydroxyalkanoates and promoting the melt flow rate of the PHA composition.

[0050] In addition, in the prior art, chemical depolymerization is usually used to reduce the molecular weight of polyhydroxyalkanoates, thereby improving the fluidity of polyhydroxyalkanoates. However, the above method is complex and it is easy to introduce a depolymerization catalyst or initiator with poor compatibility, thereby affecting the mechanical strength or other properties of polyhydroxyalkanoates. Referring to Example 1 and Comparative Example 3 and in combination with Table 2, it can be seen that relative to Comparative Example 3, the tensile strength and melt flow rate of Example 1 are slightly improved, which indicates that the modification of graphene can effectively improve the mechanical properties and coating properties of the PHA composition.

[0051] The mechanism is that in Example 1, N-(2-(isomethacryloyloxy)ethyl)-N,N-dimethyldodecane-1-ammonium bromide is grafted onto the graphene surface through coupling reaction and free radical copolymerization, which improves the dispersion performance of graphene and obtains excellent antibacterial performance. The antibacterial mechanism of N-(2-(isomethacryloyloxy)ethyl)-N,N-dimethyldodecane-1-ammonium bromide-graphene nanohybrid is that N-(2-(isomethacryloyloxy)ethyl)-N,N-dimethyldodecane-1-ammonium bromide-graphene nanohybrid contains quaternary ammonium salt components, and quaternary ammonium salts can destroy the integrity of bacterial cell membranes, interfere with metabolic processes in bacterial cells, and affect the replication and transcription of bacterial nucleic acids, so that it is more suitable for the field of packaging coating.

[0052] Referring to Example 1 to Example 4 and combining with Table 2, it can be seen that among Examples 1 to 3, Examples 3 and 4 have the best melt flow rate, which shows that the alkali metal compound selected from potassium fluorodisulfonyl imide has the best coating speed improvement effect.

[0053] The reason is that among potassium hydroxide, potassium acetate and potassium fluorodisulfonyl imide, potassium acetate and potassium fluorodisulfonyl imide contain organic groups. Therefore, compared with potassium hydroxide, potassium acetate or potassium fluorodisulfonyl imide have better compatibility with polyhydroxyalkanoates, thereby enabling the alkali metal compound to act more accurately on the ester bond of the polyhydroxyalkanoates, thereby enabling the prepared PHA composition to have a better melt flow rate.

[0054] Of potassium acetate and potassium fluorinated disulfonyl imide, potassium fluorinated disulfonyl imide has both a higher cation mass ratio and a higher flexible conjugated structure, thereby obtaining a better cation migration performance, that is, the reaction activity of potassium fluorinated disulfonyl imide is better, thereby enabling the PHA composition to still have an extremely good melt flow rate at a lower alkali metal compound addition amount.

[0055] Referring to Example 3, Example 5 and Example 6 and in combination with Table 2, it can be seen that, compared with Example 5 and Example 6, Example 3 has relatively better tensile strength and melt flow rate, which indicates that when N-(2-(isobutylene acyloxy)ethyl)-N,N-dimethyldodecane-1-ammonium bromide-graphene nanohybrid and fluorodisulfonyl potassium imide are added in the above amounts, the prepared PHA composition will have excellent composite strength, faster coating speed, excellent antibacterial properties and gas barrier properties.

[0056] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A PHA composition with high lamination speed and high paper-plastic composite strength, characterized in that: The invention comprises the following raw materials in parts by weight: 85-95 parts of polyhydroxyalkanoate, 6-10 parts of N-(2-(isobutylene oxy)ethyl)-N,N-dimethyldodecane-1-ammonium bromide-graphene nano hybrid and 0.5-3 parts of alkali metal compound, wherein the alkali metal compound is one of potassium hydroxide, potassium acetate and potassium fluorodisulfonyl imide.

2. The PHA composition with high lamination speed and high paper-plastic composite strength according to claim 1, characterized in that: The preparation method of the N-(2-(isobutylene acyloxy)ethyl)-N,N-dimethyldodecane-1-ammonium bromide-graphene nanohybrid is as follows: First, 0.4-0.6 g of γ-methacryloyloxypropyltrimethoxysilane modified graphene is dispersed in 40-60 ml of n-butanol under a nitrogen atmosphere, and then 5-10 mg of benzoyl peroxide and 0.5-1.0 g of N-(2-(isobutylene oxy)ethyl)-N,N-dimethyldodecane-1-ammonium bromide are added in sequence. The temperature is raised to 70-90°C and the reaction is continued for 24 hours. Finally, the mixture is washed and freeze-dried to obtain N-(2-(isobutylene oxy)ethyl)-N,N-dimethyldodecane-1-ammonium bromide-graphene nanohybrid.

3. The PHA composition with high laminating speed and high paper-plastic composite strength according to claim 2, characterized in that: The preparation method of the γ-methacryloxypropyltrimethoxysilane modified graphene is: First, 8-12 ml of γ-methacryloxypropyltrimethoxysilane is dissolved in 80-120 ml of methanol-deionized water solution at room temperature, and the volume ratio of methanol to deionized water is (8-10):

1. After it is fully dissolved, 0.8-1.2 g of graphene is added, the temperature is raised to 100-120°C and reacted for 12 hours, and finally washed and freeze-dried to obtain γ-methacryloxypropyltrimethoxysilane modified graphene.

4. The PHA composition with high laminating speed and high paper-plastic composite strength according to claim 2, characterized in that: The preparation method of the N-(2-(isobutylene acyloxy)ethyl)-N,N-dimethyldodecane-1-ammonium bromide is as follows: First, 15-25 mmol of dimethylaminoethyl methacrylate and 15-25 mmol of 1-bromododecane are dissolved in 4-8 ml of ethanol, then the temperature is raised to 60-80°C and reacted for 12 hours, then recrystallized in ethanol, and finally freeze-dried to obtain N-(2-(isobutylene oxy)ethyl)-N,N-dimethyldodecane-1-ammonium bromide.

5. The PHA composition with high laminating speed and high paper-plastic composite strength according to claim 3, characterized in that: The preparation method of the graphene is: First, add 2-4g of graphite flakes and 1-2g of sodium nitrate to 50-80ml of concentrated sulfuric acid, then cool the mixture to 0°C, then slowly add 5-10g of potassium permanganate to the mixture, keeping the temperature below 20°C during the addition process; After the addition is completed, the temperature is raised to 30-40°C, the reaction is continued for 20-40 minutes, and then 100-150 ml of deionized water is added dropwise, and the reaction is carried out at a temperature of 90-100°C for 12-18 minutes, and then 400-450 ml of deionized water and 2-4 ml of hydrogen peroxide are added, and finally dialyzed, filtered, washed, and freeze-dried to obtain graphene.

6. The PHA composition with high laminating speed and high paper-plastic composite strength according to claim 1, characterized in that: The alkali metal compound is potassium fluorodisulfonyl imide.

7. The PHA composition with high laminating speed and high paper-plastic composite strength according to claim 6, characterized in that: The preparation method of the fluorodisulfonyl imide potassium comprises the following steps: Preparation of potassium trifluoromethylsulfonamide: First, 95-105g of trifluoromethylsulfonamide was mixed with 450-550ml of deionized water, and then 40-60ml of potassium hydroxide aqueous solution was slowly added dropwise, and the concentration of the potassium hydroxide aqueous solution was 0.8g / ml. The mixture was stirred for 6h, and finally filtered and concentrated to obtain potassium trifluoromethylsulfonamide; Preparation of (trifluoromethylsulfonyl)(chlorosulfonyl)imide: First, 35-45g of trifluoromethylsulfonamide, 70-76g of thionyl chloride and 40-46g of chlorosulfonic acid are mixed, then the temperature is raised to 110-130°C, and the excess thionyl chloride is distilled off after reflux for 45h, and the excess chlorosulfonic acid is distilled off under reduced pressure at 90°C, and finally the temperature is raised to 120°C and distilled off under reduced pressure to obtain solid (trifluoromethylsulfonyl)(chlorosulfonyl)imide; Preparation of Potassium Fluorodisulfonyl Imide: First, 12-16 g (trifluoromethylsulfonyl) (chlorosulfonyl) imine, 10-12 g trifluoromethylsulfonamide potassium, 8-12 g pyridine and 90-110 ml acetonitrile are mixed, then the temperature is raised to 70-90 ° C and stirred for 24 hours, and then the insoluble matter is removed by suction filtration, and the filtrate is concentrated under reduced pressure to obtain a solid product; The yellow product was then washed with methyl tert-butyl ether, and then vacuum dried at 60°C for 12 hours. Then, 18-22 g of potassium phosphate and 90-11 ml of acetonitrile were added at 40°C, and the mixture was reacted for 8 hours. Finally, the insoluble matter was removed by filtration, and the filtrate was concentrated under reduced pressure to obtain solid potassium fluorodisulfonyl imide.

8. The PHA composition with high laminating speed and high paper-plastic composite strength according to claim 6, characterized in that: The PHA composition with high lamination speed and high paper-plastic composite strength comprises the following raw materials in parts by mass: 90 parts of polyhydroxyalkanoate, 8 parts of N-(2-(isobutylene acyloxy)ethyl)-N,N-dimethyldodecane-1-ammonium bromide-graphene nanohybrid and 1 part of potassium fluorinated disulfonyl imide.

9. A method for preparing a PHA composition with high laminating speed and high paper-plastic composite strength according to any one of claims 1 to 8, characterized in that: The following steps are involved: S1. First, polyhydroxyalkanoate, N-(2-(isobutyleneoxy)ethyl)-N,N-dimethyldodecane-1-ammonium bromide-graphene nanohybrid and alkali metal compound are mixed, and then added into a twin-screw extruder for melt blending, with a melt temperature of 160-170° C. and a screw speed of 300-500 r / min, followed by extrusion granulation to obtain a crude product; S2. After drying the crude product, heat it in a water bath for 1-2 hours at a water bath temperature of 40-60° C., and finally dry it again to obtain a PHA composition with high lamination speed and high paper-plastic composite strength.

Citation Information

Patent Citations

  • High-flowability polyhydroxyalkanoate composition, molded body and preparation method of high-flowability polyhydroxyalkanoate composition

    CN116855052A

  • Method of collecting highly pure polyhydroxyalkanoate from microbial cells

    CN1738904A